CIMORAME EDUCATIONAL TOURISM DEVELOPMENT STRATEGY - Susanti, Meisy Deva; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the development strategy for Cimorame educational tourism in Sumorame Village, Candi Subdistrict, Sidoarjo Regency, and to formulate a sustainable development strategy oriented towards empowering the local community. Method: The method used is qualitative descriptive with a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis framework. Result: The results show that the development of Cimorame educational tourism is carried out in stages and in a structured manner, supported by an increase in village funds each year, which are used for infrastructure improvements, the addition of water rides, and the development of agribusiness-based grape picking tourism. This strategy successfully optimizes the potential of nature, local culture, and community participation in creating an inclusive and sustainable educational tourism destination. Novelty: The novelty of this study lies in the educational tourism management model that combines recreational, educational, and economic aspects through targeted fund management and the use of social media as a promotional strategy. The results of the SWOT analysis serve as the basis for developing a development strategy that accommodates internal strengths and external opportunities, while also responding to existing weaknesses and threats, in order to realize Cimorame as a competitive and competitive community-based educational tourism icon.